Local government reform, social services and gender perspective - Roldán García, Elena; Leyra Fatou, Begoña (Investigaciones Feministas (Feminist Research), 2015)
The new legal framework for local government, the Law 27/2013 of 27 December, on Rationalization and Sustainability of Local Government (LRSAL) substantially modifies its powers and, specifically, in social services and gender perspective. Following the entry into force of this regulation, this paper provides some interpretive keys to determine, first, how it has been in previous stages the institutionalization of local social services policies, the incorporation of a gender perspective and reforms which have taken place. Secondly, it addresses briefly, the main theoretical frameworks of structuring social services and gender policies: social cohesion, inequality, mainstreaming and intersectionality. Subsequently, a critical review of the new legislation and its impact on social services is performed. It concludes with an assessment of the possibilities and uncertainties of the future of social services and gender perspective after this local reform. We are aware that the recent approval of this new legislation does not yet allow a detailed analysis of its application and its consequences, however, can be glimpsed different options to the future which constitute elements for the debate as: what kind of decisions will have to be taken in order to mitigate the negative impact on social services and gender perspective of this law, criticized by professionals and academics who do not hesitate to describe it as some vague, contradictory and incomplete.
Keywords: Social Services Policies; Local legislative reform; Gender perspective; Social cohesion.